Assessment of Patients Satisfaction and Anesthesia Related Discomfort Between Spinal Anesthesia and General Anesthesia for Cesarean Section - Hashmi, Faiqa; Zia, Aneeqa; Khan, Safdar Ali; Hussain, Tanvir; Imran, Faisal; Rehman, Sami Ur (Biological and Clinical Sciences Research Journal, 2025)
Cesarean section is a commonly performed obstetric procedure, and the choice of anesthesia—general or spinal—plays a crucial role in determining maternal comfort and satisfaction. Evaluating the differences in anesthesia-related discomfort and overall patient satisfaction between the two techniques is essential for optimizing perioperative care. Objective: To determine the frequency of general anesthesia (GA) and spinal anesthesia (SA) use in elective cesarean sections and to compare patient satisfaction and anesthesia-related discomfort between the two techniques. Methods: This quasi-experimental study was conducted at the Anaesthesia Department of National Hospital and Medical Centre, Lahore, Pakistan, from August 2024 to February 2025. A total of 127 women scheduled for elective cesarean section were enrolled and divided into two groups based on the planned anesthesia technique: Group A (GA) and Group B (SA). Patient satisfaction and anesthesia-related discomfort were evaluated 12 hours postoperatively using the Bauer Patient Satisfaction Questionnaire, which includes five Likert-scale questions. Data were collected at discharge and analyzed using SPSS version 25. Independent sample t-tests were used to compare mean scores, with p < 0.05 considered statistically significant. Results: Out of 127 participants, 63% underwent spinal anesthesia and 37% received general anesthesia. The mean discomfort score was significantly higher in the GA group compared to the SA group (4.26 ± 0.71 vs. 3.05 ± 0.82; p<0.001), while the mean satisfaction score was significantly lower in the GA group compared to the SA group (14.19 ± 1.58 vs. 15.26 ± 1.29; p<0.001). Conclusion: Spinal anesthesia was more frequently utilized and yielded significantly higher satisfaction and lower anesthesia-related discomfort compared to general anesthesia in women undergoing elective cesarean section. These findings support the preference for spinal anesthesia to enhance patient-centered outcomes in obstetric care.